Location of polyelectrolytes in swollen lipid oligobilayers - Schwörer, Felicitas; Trapp, Marcus; Silvi, Luca; Gutfreund, Philipp; Steitz, Roland; Dahint, Reiner (Langmuir, 2023)
Osteoarthritis is caused by degeneration of the cartilage, which covers the bone ends of the joints and is decorated with an oligolamellar phospholipid (PL) bilayer. The gap between the bone ends is filled with synovial fluid mainly containing hyaluronic acid (HA). HA and PLs are supposed to reduce friction and protect the cartilage from wear in joint movement. However, a detailed understanding of the molecular mechanisms of joint lubrication is still missing. Previously, we found that aqueous solutions of HA and poly(allylamine hydrochloride) (PAH), the latter serving as a polymeric analogue to HA, adsorb onto the headgroups of surface-bound 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) oligobilayers and significantly enhance their stability with respect to shear forces, typically occurring in joint movement. We now investigated the precise location of PAH chains across the lipid films in neutron reflectivity measurements, as bridging of the oligobilayers by polyelectrolytes (PEs) might be the cause for their improved mechanical stability. In a first set of experiments, we used hydrogenated PAH and chain-deuterated DMPC (DMPC-d54) to improve the contrast between the lipids and potentially intruding PAH. However, due to difficulties in distinguishing between incorporation of water and PAH, penetration into the lipid chain region could hardly be proven quantitatively. Therefore, we designed a more elaborate experiment based on mixed films of DMPC-d54 and hydrogenated DMPC, which is insensitive to water penetration into the films. Beside facilitating a detailed structural characterization of the oligolamellar system, this elaborate approach showed that PAH adsorbs to the DMPC heads and penetrates the lipid tail strata. No PAH was found in the lipid head strata, which excludes bridging of several lipid bilayers by the PE chains. The data are consistent with the assumption that PAH bridges are formed between the headgroups of two adjacent bilayers and contribute to the enhanced mechanical stability.
Gesehen am 30.01.2024